2016
DOI: 10.1038/srep36145
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization in flickering of three-coupled candle flames

Abstract: When two or more candle flames are fused by approaching them together, the resulting large flame often exhibits flickering, i.e., prolonged high-frequency oscillation in its size and luminance. In the present work, we investigate the collective behaviour of three-coupled candle flame oscillators in a triangular arrangement. The system showed four distinct types of syncronised modes as a consequence of spontaneous symmetry breaking. The modes obtained include the in-phase mode, the partial in-phase mode, the ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 20 publications
5
30
0
1
Order By: Relevance
“…Flickering also exists in multi-flame systems. Recent experimental studies [25][26][27][28][29] have reported that for candle or jet flames in pairs or arrays the flickering of each individual flame spontaneously synchronizes with each other, rendering special synchronized flickering modes. According to Kitahata et al [25], the interaction between two side-by-side oscillating flames exhibits two distinct modes, inphase and anti-phase, depending on the distance between the flames.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Flickering also exists in multi-flame systems. Recent experimental studies [25][26][27][28][29] have reported that for candle or jet flames in pairs or arrays the flickering of each individual flame spontaneously synchronizes with each other, rendering special synchronized flickering modes. According to Kitahata et al [25], the interaction between two side-by-side oscillating flames exhibits two distinct modes, inphase and anti-phase, depending on the distance between the flames.…”
Section: Introductionmentioning
confidence: 99%
“…Forrester [27] experimentally identified an initial-arch-bow-initial "worship" oscillation mode for four candles arranged within a closed loop. Okamoto et al [28] reported four distinct synchronized flickering modes for three coupled candle flames in a triangular array. Despite the complexity of these multi-flame systems, the crucial component of them is the interaction of a dual-flame system, which is largely affected by the gap distance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The retrodiction thus turns into a standard prediction: In all cases where the shutter's post-selection succeeds, the test particle is reflected from all the N-1 boxes, demonstrating the shutter's simultaneous existence in all of them. Okamoto and Takeuchi [4] have recently tested this prediction of the TSVF for N=3 in a quantum optics setup employing a novel quantum router [5] which enables the shutter and the probe photon to indirectly interact. Their results show that the shutter did not randomly occupy one of the two boxes, but rather (within experimental accuracy limitations) reflected a photon from both.…”
Section: The "Shutter Version" and Its Recent Realizationmentioning
confidence: 99%
“…Based on the Okamoto-Takeuchi [4] realization of Aharonov and Vaidman's protocol [2], our proposal for a realization of the disappearing-reappearing particle naturally follows [8].…”
Section: The Disappearing-reappearing Particle Made To Act As a Shuttermentioning
confidence: 99%